THE INFLUENCE OF WORKPLACE SPIRITUALITY AND PSYCHOLOGICAL SAFETY ON HEALTHCARE WORKERS’ SERVICE INNOVATION - Muranny Nurshyaliha Manurung; Kosasih (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of workplace spirituality and psychological safety on service innovation among healthcare workers using a literature review approach. The study is based on secondary data obtained from relevant scientific sources, including journals, books, and academic publications. The analysis focuses on identifying patterns, relationships, and key findings from previous studies related to workplace spirituality, psychological safety, and service innovation in healthcare settings. The results of the study indicate that workplace spirituality has a significant role in enhancing intrinsic motivation, meaningful work, and employee engagement, which contribute to the development of innovative behavior. Psychological safety is found to have a direct impact on service innovation by creating a work environment that encourages open communication, knowledge sharing, and risk-taking without fear of negative consequences. Both variables not only influence service innovation individually but also interact in a complementary manner. The combined effect of workplace spirituality and psychological safety creates a supportive work environment that strengthens creativity, collaboration, and continuous improvement. Healthcare workers who experience meaningful work and feel psychologically safe are more likely to generate, share, and implement innovative ideas in service delivery.